Effects of Computer-Assisted Instruction on Students' Achievement in Taiwan: A Meta-Analysis - Liao, Yuen-kuang Cliff (Computers and Education, 2007)
A meta-analysis was performed to synthesize existing research comparing the effects of computer-assisted instruction (CAI) versus traditional instruction (TI) on students' achievement in Taiwan. Fifty-two studies were located from four sources, and their quantitative data was transformed into effect size (ES). The overall grand mean of the study-weighted ES for all 52 studies was 0.55. The results suggest that CAI is more effective than TI in Taiwan. In addition, two of the seventeen variables selected for this study (i.e., statistical power, and comparison group) had a statistically significant impact on the mean ES. The results from this study suggest that the effects of CAI in instruction are positive over TI. The results also shed light on the debate of learning from media between Clark and Kozma.
Keywords: TICE; numérique